Migration among individuals with leprosy: a population-based study in Central Brazil - Christine Murto; Liana Ariza; Carlos Henrique Alencar; Olga André Chichava; Alexcian Rodrigues Oliveira; Charles Kaplan; Luciana Ferreira Marques da Silva; Jorg Heukelbach (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
This study investigates social and clinical factors associated with migration among individuals affected by leprosy. A cross-sectional study was conducted among those newly diagnosed with leprosy (2006-2008), in 79 endemic municipalities in the state of Tocantins, Brazil (N = 1,074). In total, 76.2% were born in a municipality different from their current residence. In the five years before diagnosis 16.7% migrated, and 3.6% migrated after leprosy diagnosis. Findings reflect aspects associated with historical rural-urban population movement in Brazil. Indicators of poverty were prominent among before-diagnosis migrants but not after-diagnosis migrants. Migration after diagnosis was associated with prior migration. The association of multibacillary leprosy with migration indicates healthcare access may be an obstacle to early diagnosis among before-diagnosis migrants, which may also be related to the high mobility of this group.